The study of the factors affecting phreatic line position and stability in upstream tailings dams - Parsa Alizadeh; Manouchehr Latifi (Results in Engineering)
The use of tailings dams is a common method for storing tailings. The position of the phreatic line significantly affects the stability of tailings dams. If this issue is not paid attention to, especially in tailings dams that are implemented upstream, irreparable environmental and economic damage and loss of life will be caused. In this type of dam, the position of the phreatic line depends on several factors, including the permeability of waste materials, segregation, the ability to depreciate the Excess pore pressure of waste materials, anisotropy ratio, pond location, and foundation permeability. This research aims to analyze and investigate the relative importance of the influential factors in the position of the phreatic line and, as a result, the stability of one of the most critical structures, upstream tailings dams, by examining their individual impact on the phreatic line. To make the results closer to reality, the characteristics of waste materials were collected for many tailings dams, and finally, the characteristics of the waste materials of Zhaoli Dam located in China were used in the analysis. The method involves using numerical simulations with the finite element method (FEM) to analyze the phreatic line, validated with empirical existing data. According to the analysis, the effect of different factors on the position of the phreatic line is different; among these factors, the location of the lake, matric suction, and segregation have the most significant effect on the position of the phreatic line. It is also worth mentioning that consolidation and capillary phenomena are critical and must be considered in the dam stability analysis of tailing dams.